2024
DOI: 10.3390/pharmacy12010011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Glucagon-like Peptide 1 Receptor Agonists on Obstructive Sleep Apnoea: A Scoping Review

Khang Duy Ricky Le,
Kelvin Le,
Felicia Foo

Abstract: Background: Obstructive sleep apnoea (OSA) and associated hypopnoea syndromes are chronic conditions of sleep-disordered breathing with significant sequelae if poorly managed, including hypertension, cardiovascular disease, metabolic syndrome and increased mortality. Glucagon-like peptide 1 receptor agonists (GLP-1RA) have recently garnered significant interest as a potential therapeutic, attributed to their durable effects in weight loss and glycaemic control in metabolic syndromes, such as obesity and type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A recent scoping review by Le and colleagues that reviewed total of nine studies demonstrated that there is some early evidence to suggest that that glucagon-like peptide 1 (GLP-1) receptor agonists may lead to reduction in AHI and improvement in OSA. 49 More rigorous studies are needed before these can become an adjuvant therapy in treatment of OSA.…”
Section: Treatment Of Osa In Pwcfmentioning
confidence: 99%
“…A recent scoping review by Le and colleagues that reviewed total of nine studies demonstrated that there is some early evidence to suggest that that glucagon-like peptide 1 (GLP-1) receptor agonists may lead to reduction in AHI and improvement in OSA. 49 More rigorous studies are needed before these can become an adjuvant therapy in treatment of OSA.…”
Section: Treatment Of Osa In Pwcfmentioning
confidence: 99%